Peran Perempuan dalam Industri di Aceh Barat : Studi Kasus di Sektor Pertanian dan Industri Rumah Tangga di Gampong Pasie Aceh Baru & Mesjid tuha kec. Meurebo Kab. Aceh Barat - Safitri, Mutiara; Mirandi, Rifa; Silvya, Thary; Farhan, M.; Yanti, Eva Julia; Handayani, Tri Quari (Yayasan Sagita Akademia Maju, 2025)
This study aims to explore the role of women in the industrial sector in West Aceh, especially in agriculture and home industry and to determine the dual role of housewives on resilience in the family economy in Gampong Pasie Aceh Baru, Meurebo District. In this study, the author includes the formulation of the problem to be known, namely that with the research, it can solve problems such as how the dual role of women (housewives) in meeting and improving welfare in the household economy. The method used in this study is a qualitative approach with interview and observation techniques to collect information from women who are active in both sectors. The research findings indicate that women make a significant contribution to the local economy through agricultural activities and processing household products. They not only function as workers, but also play a role as decision makers at the family and community levels. However, there are several challenges, including limited access to training and resources, and social norms that hinder their role. And each activity carried out by these housewives has different incomes depending on their respective jobs. The results of this study are expected to provide insight into the development of policies that support women's empowerment in rural areas.